Press Publishers’ Right in Hungary: Brief Empirical Report After the Implementation - Harkai, Istvan (Public Governance, Administration and Finances Law Review, 2024)
Access to information, consumption of media products and mass media have changed radically in the age of digital technologies. News gathering and aggregation platform services and social media sites have become indispensable, making news produced by press publishers available to the public in a collected, sorted and categorised form. The construction of the right of press publishers in the CDSM Directive raises a number of questions, and doubts have only been exacerbated by the Member States’ transposition. Experience to date does not yet provide scope for a precise analysis and interpretation of the impact of Article 15. Nor is it known yet in what exact framework does the new related rights be exercised in the Member States. Transposition and subsequent events do not provide answers to the most pressing questions. These include whether competition law instruments can be more effective against the dominant platform giants, which seem reluctant to reach agreements with publishers. Does it violate the principle of contractual freedom to force industry platforms to enter into Article 15 license agreements, when experience so far clearly shows that platforms would rather stop indexing content if they had to pay a fee for the content exploitation. While the intention to promote a free and diverse press, quality journalism, access to information for citizens, public debate and the development of a democratic society is more than welcome, experience so far paints a much more nuanced picture. In order to alley the doubts, this paper attempts to look into the details of the Hungarian implementation of press publishers’ right, and to outline what do the Hungarian press industry representatives think about the new neighbouring right.